1965
DOI: 10.1111/j.1651-2227.1965.tb06416.x
|View full text |Cite
|
Sign up to set email alerts
|

Antidiuretic Activity in the Plasma of Human Infants After a Load of Sodium Chloride

Abstract: It is known that under comparable conditions of dehydration newborn and infant animals are unable to form urine of as high an osmotic concentration as adult animals [S, 171. The difference in concentration capacity in the young and in the adult is more pronounced the less mature the newborn. This low concentration capacity has also been described for human infants, and it has been stated that the mean maximum limits of osmolarity in children in the first weeks after birth are about 800 mOsm/L, which means that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1974
1974
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…This may be regarded as a criterion of good reabsorption from the intestine even in the newborn infant. An increase in serum sodium 20 minutes after an oral NaCl administration has also been demonstrated by others (34).…”
Section: Administration Of Different Loadssupporting
confidence: 71%
See 1 more Smart Citation
“…This may be regarded as a criterion of good reabsorption from the intestine even in the newborn infant. An increase in serum sodium 20 minutes after an oral NaCl administration has also been demonstrated by others (34).…”
Section: Administration Of Different Loadssupporting
confidence: 71%
“…The diluting some low values were observed, i.e. [25][26][27][28][29][30][31][32][33][34][35] capacity or free water cIearence which is also an index of distal tubular sodium re-:b (mean * 1 SD, ml/hour/1.73 m2.) absorption (5) was supernormal in preterm infants and in newborn full-term infants in the immediate neonatal period (I, 11).…”
Section: Diluting Capacitymentioning
confidence: 99%
“…The physiological basis for this is incompletely understood but may include distal renal tubular unresponsiveness to aldosterone [22], reduced proximal renal tubular sodium absorption increasing the distal tubular sodium load [22], increased renal urinary sodium losses [22], counteracting the effect of elevated atrial naturetic peptide [10], increased sympatho-adrenergic activity [12] or reduced antidiuretic hormone levels [13].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors might be responsible for these changes in renal concentrating performance. Thus it has been shown that there is a progressive lengthening of Henle's loops during the first weeks of life [5,8], According to some investigators, the availability of the antidiuretic hormone is decreased in the first weeks of extrauterine life, which might contribute to the lower renal concentration ability [10,12]. However, as just a little antidiuretic activity is needed to induce near maximal antidiuresis [9] the decreased availability is probably not the limiting factor.…”
Section: Postnatal Development O F Renal Concentration Capacitymentioning
confidence: 99%